Policy Formulation for Indonesia's Criminal Action of Corruption as Ius Constituendum - Ardi, Muhamad Khalif; Nurwinardi, Nurwinardi; Musa , Alnour Abobaker Mohamed (Wacana Hukum, 2024)
The objective of this study is to ascertain Bharada Eliezer's stance on Decision Variety: 798/Pid.B/2022/PN.Jkt.Sel, which pertains to the position of Justice Collaborator police officers, as well as the Police Code of Ethics Decision concerning Bharada Eliezer's police status. This study employs a normative juridical research methodology, together with conceptual and statutory techniques. Essentially, when an individual unlawfully ends another person's life, it constitutes a violation of human rights and a denial of the right to life, particularly when the perpetrator is a law enforcement officer who continues to serve in the police force. However, in this particular case, the judge and the responsible official overseeing the KKEP hearing must take into account the defendant's status as a justice collaborator, who is feared by irresponsible parties and at risk of abuse. Ensure that all personnel of the National Police receive guidance to prevent them from engaging in actions that contravene laws, regulations, and the ethical standards of the police profession, which could damage the reputation of the police organization or agency. It is necessary to revise the requirements and guidelines for justice collaborators due to certain criminal offenses that pose a threat to the state and involve exceptional crimes. Justice collaborators play a crucial role in clarifying initially ambiguous criminal offenses.